PERBANDINGAN OBJEKTIVITAS BAHASA PADA SURAT KABAR TERBITAN LOKAL DAN TERBITAN PUSAT - Lina Andini (Asas: Jurnal Sastra, 2013)
This study departs from the background of many mass media circulatingin the community, especially newspapers. With that news consumptionbecomes the main reason people need newspapers. Readers expect newsobtained from newspapers absolutely factual and actual language useobjective. Formulation of the problem in this study were: (1) how theobjectivity of the language used in the local newspaper publications andnewspapers published by the center? (2) Is objectivity languagenewspaper the central issue is different from the language of objectivityon the issue of the local newspaper? (3) Which of these two is the moreobjective issue from the standpoint of language use? This study aims to:describe objectivity language publications in local newspapers andpublications centers. The method used in this research is descriptivequalitative method, which applies a content analysis method byanalyzing the descriptive language of objectivity. The subjects wereeditorial in the newspaper Kompas, Indonesia Seputar, Alert andAnalysis published in one week in November of 2012 edition. In thisstudy, the researcher is the main instrument is the planners,implementers, data collectors, analysts, interpretation of data, andreporting research results. Another instrument used in this study is atable of data discovery functions for grouping data. The results showed ahigh degree of subjectivity element contained in the local newspaperpublications (Alert and Analysis) then the central issue of the newspaper(Kompas and Around Indonesia) with the amount of data acquired isPDF Creator - PDF4Free v3.0 http://www.pdf4free.comWatchful 23 element of subjectivity, subjectivity analysis of 22elements, 20 elements of subjectivity Compass and Around Indonesia 17element of subjectivity. From the data analysis it can be concluded thatthe newspaper published by the center is more objective than the localnewspaper.Keyword: objectivity of the language, newspaper